Evaluation of the etiology of epilepsy and/or developmental delay in children via next-generation sequencing: a single-center experience - Kava, Handan; Akgun-Dogan, Ozlem; Yesilyurt, Ahmet; Alanay, Yasemin; Isik, Ugur (Frontiers in Pediatrics, 2025)
BackgroundWe aimed to understand the genetic etiology in children presenting with epilepsy and/or developmental delay by using next-generation sequencing (NGS).Materials and methodsWe included children presenting to our pediatric neurology clinic with a diagnosis of epilepsy and/or developmental delay between January 2019 and December 2021. We evaluated the patients using the NGS equipment in our genetic laboratory.ResultsIn total, 90 patients were included in the study. Twenty (34.4%) out of 58 patients who had undergone whole-exome sequencing (WES) had pathogenic or likely pathogenic (P/LP) variants and 11 (18.9%) had variants of unknown significance (VUS). Five (41.6%) out of 12 patients who had undergone whole-genome sequencing had P/LP variants and 5 (41.6%) had VUS. Eleven (55%) out of 20 patients who had undergone WES and chromosomal microarray had P/LP variants and 2 (10%) had VUS. Twenty-six novel variants were described. Twelve patients (13.3%) were diagnosed using a known specific treatment.ConclusionNGS aids in precisely diagnosing children with epilepsy and/or developmental delay. Furthermore, it provides a correct prognosis, specific treatment methods, and a multidisciplinary approach.